التحرير والتقرير في أسانيد التفسير بالمأثور : دراسة تحليلية للطبقات الثلاث الأول - عزران، عبد العزيز فرج حمد علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The research aims to highlight on the issue of the different references of Shariah techniques for the acceptance and rejection of the narration and its narrator based on analytical and inductive approach. Every Shariah techniques have principles upon which the competent scholars built the ruling of acceptance and rejection of narrations and its narrator based on the models from the category of companions, their followers and followers of their followers, may Almighty Allah be pleased with them. The researcher established the differences in the principles of Shariah, even though there are overlapping between them, yet, some shariah principles cannot rule on the general techniques as observed in the work of some editors of classical scholars of exegeses of the Glorious Quran and their rejections of the approaches of those whom comments on the scholars of the science of discrediting and endorsement of hadith. The researcher studies the interpretative narratives models of selected companions' and carefully probe into the number of narrators to identify those that are are elevated and cut-off. Then he mentioned the individual characteristics of each companion and mentioning the approaches and contents of their narration in the context of the trustworthy and the vulnerable narrators. Then the researcher evaluates the categories of the companions and the establishment of the correct interpretation among them. In the same way, the researcher explores categories of the followers and their followers, may Almighty Allah have mercy on them. The researcher also established that the weak narrator is not rejected simply based on the weakness in the chain of transmission, because there is a difference between the narration of as-sadr and the narration of as-satr from the book. Also, the researcher proves the poor assessment of the hadith terminologists as they say that the loose (mursal) hadith is from the weak sections of hadith by criticizing the narrators of the followers, may Allah have mercy on them. The researcher has concluded this study with some recommendations.